Central Hyperthyroidism due to Thyroid-Stimulating Hormone-Secreting Pituitary Microadenoma in an Adolescent Boy: Case Report and Review of the Literature - Le Hoang Bao; Nguyen Minh Duc; Phan Cong Chien; Thieu-Thi Tra My; Tran Viet Thang; Tran Quang Nam (Case Reports in Endocrinology)
Thyroid-stimulating hormone- (TSH-) secreting pituitary adenoma (TSH-oma) is a rare cause of secondary hyperthyroidism and can be misdiagnosed as primary hyperthyroidism. We report a case of a 15-year-old male patient who was one of two monozygotic twins and exhibited hyperthyroidism syndrome. The laboratory results showed secondary hyperthyroidism, with increased levels of free T3 (FT3) and free T4 (FT4) and no TSH inhibition. Magnetic resonance imaging (MRI) and histopathological examination of the pituitary gland confirmed pituitary microadenoma. The patient was treated with methimazole, propranolol, and somatostatin analogs to restore euthyroidism before undergoing an endoscopic transsphenoidal resection of the pituitary tumor. After surgery, the hyperthyroidism symptoms improved, thyroid hormones normalized, and MRI of the pituitary gland showed the complete removal of the tumor with no recurrence after 2 years of follow-up.